Leadership Crises and Implications for Sustainable Development in Nigeria - Duyile, Praise Fisayo (ABUAD Journal of Social and Management Sciences, 2023)
Nigeria has indeed struggled with socio-economic growth and development since its emancipation from colonial domination, trundling within a cycle of rent-booms, recessions, and even economic collapse. This study argues that the root cause of these socio-economic problems is poor leadership, marked by oppression, exploitation, nepotistic governance structure, electoral violence, and pervasive and systemic corruption. These negative indices have plunged the nation into a state of protracted violent conflicts, extreme poverty, weak infrastructure, rising youth unemployment and restlessness, untimely deaths, and multifaceted humanitarian crises. The paper examines the nature of political leadership and its bourgeoning effects on the development of Nigeria, using the predatory state paradigm as a guide. Relying on secondary data, the study asserts that the Nigerian ruling elites are aware of the dire situation of the country but keep aloof in order to maintain their corrupt grip on power. The study maintains that visionary leadership needs to be strategically harmonised with the abundant resources of the nation for it to get back on the track of development and instill confidence in a disenchanted populace.